Management practices and milk quality in dairy goat farms in Northern Italy. Issue 1 (2nd January 2019) - Sandrucci, Anna; Bava, Luciana; Tamburini, Alberto; Gislon, Giulia; Zucali, Maddalena
Abstract: A large-scale survey was conducted on 173 dairy goat farms in Northern Italy to provide an updated view on farm management practices and to investigate relations among management factors, herd traits and milk yield and quality with particular focus on milk somatic cell count (SCC) and milk fat/protein reversion syndrome. Monthly individual milk analyses (fat, protein and lactose percentages, SCC) and bulk tank milk analyses (fat, protein and lactose percentages, standard plate count (SPC), urea and casein) from 91 farms out of the 173 farms were collected for a year. Farming systems showed wide variability and were characterised by the coexistence of intensive farms adopting advanced technologies and extensive traditional ones. Average milk production was 1.25 kg/milking with high variability, significantly influenced by days in milk, month of kidding, herd size and parity. Out-of-season breeding was predicted to cause a slight reduction of milk production. The reversion syndrome between milk fat and protein contents affected more than half of samples. It worsened after 100 d of lactation and occurred earlier during lactation when kidding was in the late season (April–June) compared to kidding in the first months of the year. The defect was associated with high SCC in milk. The yearly average milk SCC was 5.8 log10 cells/mL; it was higher at the end of lactation and in goats kidding in the late season. A negative relationship between SCC and milk yield was found with an estimated loss of 0.23 kg per milking for each additional point of log10 SCC.